Distinctive Effects between Hydrothermal and Ultrasound Synthesized SnO2 Nanoparticles on Ceramic Bi1.6Pb0.4Sr2Ca2Cu3O10+δ Superconductor - Pham, Pham The; Anh, Do Kim Thi; Thien, Nguyen Duy; Linh, Vu Hoang; Dung, Le Hoang; Man, Nguyen Khac; Duc, Tran Hai (VNU Journal of Science: Mathematics - Physics, 2024)
The effect of additions of two series of SnO 2 nanoparticles synthesized using two different methods on crystal structure and superconductivity of Bi 1.6 Pb 0.4 Sr 2 Ca 2 Cu 3 O 10+δ (BPSCCO) superconductors was investigated. Two series of spherical SnO 2 nanoparticles were synthesized independently by using ultra-sonication (US-SnO 2 ) and hydrothermal (HT-SnO 2 ) methods. Polycrystalline samples of (Bi 1.6 Pb 0.4 Sr 2 Ca 2 Cu 3 O 10+δ ) 1−x (SnO 2 ) x , where x ranged between 0, 0.002 and 0.004, were fabricated by the solid-state reaction method. X-ray diffraction patterns showed a decrease in the volume fraction of the Bi-2223 and an increase in that of the Bi-2212 phases. Scanning electron microscopy images presented the “needle-like blossom” on the surface of the US-SnO 2 doped samples, while the phenomenon was not found on the HT-SnO 2 doped samples. The T c was decreased extremely with US-SnO 2 doping while slightly HT-SnO 2 nanoparticle-doped samples. The field dependence of J c , J c ( B ), showed the opposite tendencies on two series of samples: J c ( B ) was enhanced on the HT-SnO 2 nanoparticle-doped samples, and that was decreased on UT-SnO 2 nanoparticle-doped samples. The application of the Dew-Hughes model to explore the flux pinning mechanism exhibited that the point-like pinning centers were dominant on the HT-SnO 2 doped samples. On US-SnO 2 doped samples, however, the additional pinning center type was not found and could be explained by the observed over-sized SnO 2 nano-needle.